Dark Sweet Cherry (Prunus Avium L.) Phenolics Induce Apoptosis and Inhibit Invasion on Breast Cancer MDA-MB-453 Through MAPK-dependent and Independent Pathways (P05-007-19). (13th June 2019) - Layosa, Marjorie Anne; Lage, Nara; Talcott, Susanne; Talcott, Stephen; Atienza, Liezl; Chew, Boon; Noratto, Giuliana
Abstract: Objectives: Dark sweet cherry (DSC) contains a rich mixture of phenolics reported to exert anti-cancer and anti-metastasis activities. We aimed to investigate the underlying mechanisms by which DSC phenolics in whole extracts (WE) and fractions enriched in anthocyanins (ACN) or procyanidins (PCN) decrease proliferation and invasion on the HER2 + breast cancer MDA-MB-453 cells. Methods: MDA-MB-453 cells were treated with DSC phenolics in WE, ACN, and PCN obtained by solid phase extraction (SPE) at doses that inhibited cell growth by 50% for 24 h. Protein expression over 24 h was assessed by western blots and invasion and metastasis potential were assessed with cell invasion and cell motility assays. Results: DSC phenolics in WE, ACN, and PCN targeted intrinsic and extrinsic apoptotic pathways as shown by caspase-8 cleavage and cytochrome c/bax upregulation that culminate in caspase-9, -3, and PARP cleavage. In addition, a sustained activation of mitogen activated protein kinases (MAPKs) pathway was induced through ERK1/2 and p-38 phosphorylation with order of potency ACN ≥ PCN > WE. The crosstalk of MAPK-apoptotic pathways were confirmed with ERK1/2 and p-38 inhibitors that partially abrogated cytochrome/bax upregulation. In addition, DSC phenolics downregulated phosphoinositide 3-kinase (PI3K) signaling pathway, which act as key regulator in cancer proliferation and metastasis, and was accompanied by cell motility inhibition. ERK1/2 and p-38 inhibitors did not reverse cell motility and invasion reduction exerted by DSC phenolics. Conclusions: DSC phenolics target pro-apoptotic intrinsic/extrinsic, and cell growth/invasion mechanisms involving PI3K and MAPK pathways. ACN showed the most consistent induction of apoptotic markers and contributed to MAPK sustained upregulation with potency ACN ≥ PCN > WE. This MAPK upregulation contributed to the intrinsic apoptotic pathway but not to the PI3K/proliferation/invasion pathways. Funding Sources: This work was supported by the Northwest Cherry Growers.